A review of PV–T systems: Thermal management and efficiency with single phase cooling. (December 2015) - Reddy, Sohail R.; Ebadian, Mohammad A.; Lin, Cheng-Xian
Highlights: Recent advances in hybrid solar photovoltaic/thermal (PV/T) systems are reviewed. Thermal management and efficiency of single phase cooling techniques are summarized. Needs in future research in this subject are discussed. Abstract: In recent years, various methods of thermal management in photovoltaic–thermal (PV–T) systems have been investigated by researchers due to its importance in the system's overall efficiency improvement. In this paper, advances in the cooling of the PV–T systems have been reviewed, with emphasis on the cooling techniques based on single phase flows. In addition to the analysis of cooling media, various implementations of cooling methods such as active and passive cooling techniques are summarized. In light of most attempts at analysing cooling configurations through experimentation, the review also discussed the analytical models that are currently being used. Numerous findings of previously conducted research have been discussed.